Evaluating a Psychoanalytically-Informed Training Program for Personality Development among University Staff in Iraq: A Freudian Framework - Naamat, Arian Tatar (Jurnal Theologia, 2025)
In modern organizational settings, unresolved psychological conflicts and dysfunctional personality traits among employees often hinder productivity, workplace harmony, and overall institutional performance. This study addresses the critical need for deeper psychological interventions by exploring the effectiveness of a training program based on Freudian psychoanalysis in developing personality traits among university employees. The research aimed to design and evaluate a psychoanalytically-informed training intervention targeting core aspects of personality such as self-awareness, emotional regulation, defense mechanisms, and interpersonal functioning. Employing an experimental one-group pre-test/post-test design, the study involved 16 purposively selected employees from the University of Zakho. Participants underwent a four-week training program consisting of 12 intensive sessions. A validated Personality Traits Development Scale (PTDS) was used to assess personality changes before and after the intervention. Statistical analysis revealed significant improvements in post-test scores compared to pre-test scores, with a very large effect size (Cohen's d = 2.32), indicating the program's substantial impact. These findings highlight the power of psychoanalytic interventions in organizational development by fostering meaningful personality transformation rather than superficial behavioral adjustments. The study contributes novel empirical evidence to the field of workplace psychology, advocating for the integration of depth psychology into team member development initiatives across diverse cultural and institutional contexts